Conversion of banana peel into diverse valuable metabolites using an autochthonous Rhodotorula mucilaginosa strain - Torres Álvarez, Dagoberto; León Buitimea, Angel; Albalate Ramírez, Alonso; Rivas García, Pasiano; Hernández Núñez, Emanuel; Morones Ramírez, José Rubén (Bio Med Central, 2022)
Low-cost substrates are an exciting alternative for bioprocesses; however, their complexity can affect microorganism metabolism with non-desirable outcomes. This work evaluated banana peel extract (BPE) as a growth medium compared to commercial Yeast-Malt (YM) broth in the native and non-conventional yeast Rhodotorula mucilaginosa UANL-001L. The production of carotenoids, fatty acids, and exopolysaccharides (EPS) was also analyzed. Biomass concentration (3.9 g/L) and growth rate (0.069 g/h) of Rhodotorula mucilaginosa UANL-001L were obtained at 200 g/L of BPE. Yields per gram of dry biomass for carotenoids (317 µg/g) and fatty acids (0.55 g/g) showed the best results in 150 g/L of BPE, while 298 µg/g and 0.46 mg/g, respectively, were obtained in the YM broth. The highest yield of EPS was observed in 50 g/L of BPE, a two-fold increase (160.1 mg/g) compared to the YM broth (76.3 mg/g). The fatty acid characterization showed that 100 g/L of BPE produced 400% more unsaturated compounds (e.g., oleic and ricinoleic acid) than the YM broth. Altogether, these results indicate that BPE is a suitable medium for producing high-value products with potential industrial applications.